Single-port robotic retroperitoneoscopic nephroureterectomy: Technical approach and recommendations for patient selection - Benjamin Yu; Richard E. Link (Urology Video Journal)
Introduction: The Da Vinci single port (SP) robotic system has emerged as a valuable platform for minimally invasive urologic surgery in the past decade. While adoption has been growing rapidly for procedures such as pyeloplasty, partial nephrectomy and radical/simple prostatectomy, its application to retroperitoneal nephroureterectomy has been less thoroughly explored. Here, we describe a retroperitoneoscopic approach to a simple nephroureterectomy using the Da Vinci SP robot and low anterior access. We focus on patient selection, advantages of regionalized SP surgery, and technical tips for operative efficiency and safety. Patient Case: Our patient is a 62-year-old female with recurrent urinary tract infections, chronic right flank pain, severe right hydroureteronephrosis and renal atrophy secondary to a chronically obstructing ureteral stone. Using a low anterior retroperitoneal SP approach, we were able to navigate complex hilar anatomy and perform a simple nephroureterectomy. The patient had no intraoperative complications and an excellent post-operative recovery. Discussion: Proper patient selection is crucial to the success of the retroperitoneal SP approach. The SP system is ideally suited for confined retroperitoneal spaces and smaller specimens, enabling efficient nephroureterectomy through a single incision with reduced patient morbidity. While the SP platform has some limitations, such as fewer available instruments and reduced retraction strength, its advantages in well-selected cases include easier and reproducible access to the renal anatomy, decreased operative time, reduced hospital stays, and improved recovery. This case illustrates the potential for single-port retroperitoneal nephroureterectomy as a minimally invasive alternative to traditional multiport or transperitoneal approaches.